Benzofurocaine: effects on experimental periodontitis, anti-diabetic activity and molecular mechanisms of action - Pavel A. Galenko-Yaroshevsky; Viktor L. Popkov; Karine A. Bedrosova; Leonid A. Faustov; Galina V. Sukoyan; Andrej V. Zadorozhny; Ol'ga N. Gulevskaya; Aleksandr V. Uvarov; Valeriya S. Dobrodomova (Belgorod National Research University, 2019)
Introduction: A promising compound for the treatment of inflammatory periodontal diseases is benzofuracaine (BFC). BFC has pronounced anti-inflammatory, analgesic, reparative, hypoglycemic and other effects. Objective: To assess the influence of benzofuracaine on experimental periodontitis and to study its antidiabetic activity and molecular mechanisms of action Materials and methods: The work was performed on 232 white nonlinear rats of both sexes and 55 male mice. To assess the effect of BFС on experimental periodontitis, the amount of gingival fluid (AGF) was determined, an in-depth morphofunctional study of periodontal tissues was conducted, as well as the study of the biochemical composition of the gingiva and blood. Antidiabetic properties were studied using the glucose tolerance test (GTT), as well as the assessment of endothelium-dependent vasodilation and transmembrane K+-currents on an isolated aortic segment of rats with streptozotocin-induced diabetes mellitus (DM). Results and discussion: In experimental periodontitis, BFC improves the morphological picture and decreases AGF, increases the level of blood microcirculation in the attached gingiva, has a normalizing effect on the prekallikrein-kallikrein system, reduces the synthesis of bradykinin, proinflammatory cytokines and PGE2, increases the level of VEGF, reduces the level of endothelin-1, increases the ATP content and NADH-ubiquinone-reductase activity, exhibits antioxidant properties, reduces the content of nitrosothiols and NO metabolites (NO2/NO3), increases the level of transferrin; when conducting a glucose tolerance test in mice, it reduces the level of glucose in the blood, but in this respect is inferior to glibenclamide, has a hypoglycemic effect in the early stages of diabetes (30 days), tends to restore endothelium-dependent dilatation of smooth muscle cells (SMC) of the aorta and does not affect the functioning of the K+-channels of the aortic SMC. Conclusion: BFС is an effective drug for the treatment of periodontitis and can be recommended for further preclinical and clinical studies.